Self-care practices among hypertensive patients at the primary health care centers in Unaizah city, Saudi Arabia - Siam, Bahia Galal Abd El-Razik; Aldakeel, Hind Kaliefah; Alrasheeday, Awatif M.; Alsaqri, Salman H.; Alshammari, Bushra; Alshammari, Farhan (Frontiers in Medicine, 2024)
Background This study assessed the self-care practices among hypertensive patients at the primary health centers in Unaizah city, Saudi Arabia. Methods This cross-sectional study was conducted in 2023, at all primary healthcare centers in Unaizah city. A total of 372 hypertensive patients, aged 18 and older, who had been on follow-up care for at least 6 months were randomly selected using a cluster sampling method. Data regarding socio-demographics, health history, and hypertensive self-care practices (H-SCALE) were collected using a validated questionnaire. Results The mean age of the participants was 41.4 ± 9.6 years. Of them, 34.1% were males and 65.9% were females. Only 14.0% were smokers, 55.9% had hypertension for less than 1 year, and 53.8% did not monitor their blood pressure. None of them was addicted to any substance or using alcohol. The most commonly associated chronic disease among the participants was hyperlipidemia (61.3%), followed by diabetes mellitus. The participants were most likely reported engaging in weight management-related self-care activities, followed by healthy diet activities, and medication adherence. The H-SCALE scores increased as the frequency of engagement in self-care activities increased. There were significant differences in H-SCALE scores based on age, gender, education level, and employment status. Conclusion Engaging in self-care activities is associated with better self-care behavior. Age, gender, education level, and employment status are significant predictors of hypertension self-care behaviors. Healthcare providers should educate hypertensive patients on blood pressure monitoring and integrated management of hypertension and other chronic diseases.